2022
DOI: 10.1002/jcph.2024
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of C‐Reactive Protein and Albumin for Temporal Within‐Individual Pharmacokinetic Variability of Voriconazole in Pediatric Patients Undergoing Hematopoietic Cell Transplantation

Abstract: Voriconazole is a widely used antifungal agent in immunocompromised patients, but its utility is limited by its variable exposure and narrow therapeutic index. Population pharmacokinetic (PK) models have been used to characterize voriconazole PK and derive individualized dosing regimens. However, determinants of temporal within-patient variability of voriconazole PK were not well established. We aimed to characterize temporal variability of voriconazole PK within individuals and identify predictive clinical fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Other variables, such as ALT, ALP, and glucocorticoids, were found to be significant covariates in other studies and were excluded from our study owing to minor variations in OFV (∆OFV < 3.84) 34,36,39 . ALB was the significant covariate for the CL of voriconazole, which was consistent with the previous studies 17,18,40 . Wei et al 41 showed that low ALB levels significantly correlated with the supratherapeutic voriconazole Cmin.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Other variables, such as ALT, ALP, and glucocorticoids, were found to be significant covariates in other studies and were excluded from our study owing to minor variations in OFV (∆OFV < 3.84) 34,36,39 . ALB was the significant covariate for the CL of voriconazole, which was consistent with the previous studies 17,18,40 . Wei et al 41 showed that low ALB levels significantly correlated with the supratherapeutic voriconazole Cmin.…”
Section: Discussionsupporting
confidence: 85%
“…The IIV of the CL in this study was 57%, which were lower than those of other paediatric studies (66.5%–117.4%) 30 . The RSV was 41.7%, similar to other studies (20.2%–58.2%) 18,23,27,28 . In addition, the shrinkage values of IIV and RSV were 7.65% and 13.98%, respectively, both below 20%, indicating that the model is stable.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Hypoalbuminemia is also one of significant characteristics in these patients, which likely to have been caused by an imbalance between ALB synthesis and catabolic rate, and secondary to an active inflammation ( Chantharit et al, 2020 ). Hypoalbuminemia increases VRC plasma unbound drug concentration which may lead to drug-related adverse reactions ( Khan-Asa et al, 2020 ; Yuan et al, 2020 ; Takahashi et al, 2021 ). In this study, hypoalbuminemia did not show to be a significant covariate of VRC plasma exposure.…”
Section: Discussionmentioning
confidence: 99%